Simulation and performance of cyclic codes by using QPSK and MSK modulation technique in communication system / Aminnoorrashid Abd Kudus - Abd Kudus, Aminnoorrashid (2004)
This project highlights the simulation performance of cyclic codes by using QPSK and MSK modulation technique in communication system. Noise reduction and information message recovery are the important aspect in designing a communication system instead of speed and accuracy in transmitting information message. For this project the communication network model use Matlab version 6.5.1 programmed and the model consist of transmitting, channel and receiver. The messages are encoded using cyclic codes and then modulated using QPSK or MSK. At the receiver, the signal is demodulated by using QPSK or MSK. Then the system make the correction forward error correction (FEC) requires a one-way link only and decoded using cyclic codes to produce the message.